Wizerunek Protesilaosa w XIII liście ze zbioru „Heroides” Owidiusza - Bobrowski, Antoni (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The story of Protesilaus, the first Greek warrior to die at Troy, is recounted in just a few lines in the second book of the Iliad; Homer adds that his grieving widow, named Laodamia, remained in her homeland. Over time, the original version was augmented with additional narrative elements, although the precise course of the literary tradition is difficult to discern. In the 1st century BC, this narrative thread of tragic love and death was explored in Rome by three poets: Catullus, Propertius, and Ovid. This paper deals with aspects of the literary portrayal of Protesilaus in Letter XIII (Laodamia to Protesilaus), which is part of Ovid’s Heroides.